COMPARISON OF UNIVERSITIES’ SCIENTIFIC PERFORMANCE USING BIBLIOMETRIC INDICATORS - Ming, Huang Wang; Hui, Zhen Fu; Yuh, Shan Ho (Malaysian Journal of Library and Information Science, 2011)
The scientific performance of National Taiwan University (NTU) and Peking University (PKU) were compared by two indicators, namely citations per publication and h-index, based on the data extracted from the Science Citation Index Expanded (SCI-Expanded), Social Science Citation Index (SSCI), and Arts & Humanities Citation Index (A&HCI) Web of Science from 2000 to 2009. Analyzed aspects covered publication outputs, publication patterns, and international and inter-institutional collaborations of the two universities. The two universities were in the same scale based on the number of publications. Articles from electrical and electronic engineering dominated the other articles in NTU while PKU researchers published a great number of articles in the basic science fields. Material science was the new field for these two universities. The USA had the greatest number of collaborated articles accounting for 15% and 12% of total articles with NTU and PKU respectively. Article impact followed a decreasing order of international collaboration, inter-institutional collaboration, and independent articles for both universities. PKU articles had higher visibility. In addition, the Essential Science Indicators were applied to investigate the research activities of NTU and PKU